الإشاريّات التّداوليّة في ديوان "أحزان صحراوية" للشّاعر تيسير السبول /Pragmatic Deixis in The Collected Poems “Desert Sorrows” by the poet Tayseer al-Subul - Hana Ibrahim Mohammad ALAmayreh, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: تعدّ التداولية من الدراسات الألسنية الحديثة التي تهتمّ بالسياق النصّي، والإشاريّات فرعُ من فروع التداولية التي تهتم بالمعنى المراد داخل السياق بين المرسل والمتلقي، وهذا المفهوم الألسني يجمع كل العناصر اللغوية التي تحيل مباشرة على المقام، من حيث وجود الذات المتكلمة أو الزمن أو المكان؛ حيث ينجز الملفوظ والذي يرتبط به معناه. وفي هذا البحث درسنا الإشاريات التداوليّة في شعر تيسير السبول في ديوانه أحزان صحراوية. بدأت الدراسة بتوضيح مصطلح الإشاريات لغة واصطلاحاً، ثم كشفت عن الإشاريات الموجودة في الديوان، وهي الإشاريات الشخصية، والاجتماعية والزمانية والمكانية، ووضّحت أهميّة هذه الإشاريات في الكشف عن المعنى النصّي، واتّبع البحث المنهج الوصفي التحليلي، ومن ضمن نتائج البحث أن الشاعر أكثر في ديوانه من توظيف الإشاريّات المكانية للتعبير عن حجم الخسارة للأمكنة العربية المسلوبة، وكان توظيف الإشاريات المكانية والشخصيّة من أكثر الإشاريّات توظيفاً في هذا الديوان . الكلمات المفتاحية: تيسير السبول، العناصرالإشارية، التداولية، الشعر، السياق. Abstract: Pragmatics is one of the modern linguistic studies that are concerned with the textual context, while deixis is a branch of pragmatics that is concerned with the intended meaning within the context between the sender and the receiver. This linguistic concept combines all the linguistic elements that directly refer to the context, in terms of the availability of subject, time, or place, where the sender sends the verbal message together with the underlying meaning. In this research, the pragmatic deixis was studies in the poetry of Tayseer al-Subul through his collection named "Dessert Sorrows”. Using descriptive analytical approach.the study began by clarifying the term deixis linguistically and idiomatically and then revealed the deixis in the collection, which are personal deixis, social deixis, temporal deixis, and spatial deixis. The study demonstrated the importance of these deixis in revealing the textual meaning. Besides that, the poet uses spatial deixis more often in his poetry to express the extent of the loss of the stolen Arab places, and the use of spatial and personal deixis are of the most employed signs in this collection. Keywords: Tayseer al-Subul, deixis elements, pragmatics, poetry, context. Abstrak: Pragmatik ialah salah satu kajian linguistik moden yang mementingkan konteks bagi sesuatu teks. Manakala deiksis adalah cabang pragmatik yang mementingkan makna yang dimaksudkan dalam konteks antara pengirim dan penerima. Konsep linguistik ini menghimpunkan semua unsur linguistik yang merujuk kepada konteks secara terus dari segi wujudnya zat penutur, masa atau tempatya. Penutur bukan saja menghasilkan lafaz yang terungkap dengan kata-kata malah penutur juga menghasilkan makna tersirat yang terkait dengan kata-kata tersebut. Kajian ini mengkaji deiksis pragmatik dalam puisi Tayseer al-Subul dalam koleksinya yang berjudul (Kesedihan Padang Pasir). Menggunakan kaedah deskriptif dan analisa, kajian dimulakan dengan menjelaskan definisi deiksis secara bahasa dan istilah, kemudian membahasakan tentang jenis-jenis deiksis dalam koleksi (Kesedihan Padang Pasir) iaitu deiksis peribadi, sosial, masa dan tempat. Kajian juga menjelaskan kepentingan deiksis dalam mengungkap makna teks. Antara dapatan kajian ini adalah penyair banyak menggunakan deiksis tempat bagi menggambarkan saiz kerugian bagi tempat-tempat di negara Arab yang dirampas. Penggunaan deiksis tempat dan watak adalah kiasan yang paling banyak digunakan dalam koleksi ini. Kata kunci: Taysir al subul. unsur deiksis, pragmatik, puisi, konteks.